Heterogeneous Adjustments of Labor Markets to Automation Technologies - Fabien Petit; Florencia Jaccoud; Tommaso Ciarli (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines the labor market adjustments to four automation technologies (i.e. robots, communication technology, information technology, and software/database) in 227 regions across 22 European countries from 1995 to 2017. By constructing a measure of technology penetration, we estimate changes in regional employment and wages affected by automation technologies along with the reallocation of workers between sectors. We find that labor market adjustments to automation technologies differ according to i) the technology involved, ii) the sector of penetration, iii) the sectoral composition of the region, and iv) the region's technological capabilities. These adjustments are driven largely by the reallocation of low-paid workers across sectors.
Keywords: J21; O33; R23; 330; automation technology; labor market; employment reallocation; sectoral composition